(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
This issue will dedicate its efforts to show a snapshot of all the theoretical and artistic practices that start and take the Internet as a social process of live exchange. A set of practices that use information flows as a form of social architecture, and that are capable of building knowledge from the circulation and collective spill of multiple knowledge. A principle of online action that ceases to be a means of transmission and becomes a support for thought and raw material for experimentation. If the traditional artist found his source of inspiration in nature, today we must take the internet as a plural space of events where space for representation, time, authorship, content, audience, artificial intelligences, and other manifestations make up a new definition of art. The flows of the images in networks move us away from the old single-channel learning model that prepared us to be operators (time alienated), and they take us into a new paradigm where we are protagonists of our time.